Women in Numbers Europe Research Directions in Number Theory - Bertin, Marie José; Bucur, Alina; Feigon, Brooke; Schneps, Leila (Association for Women in Mathematics Series, 2015)
Covering topics in graph theory, L-functions, p-adic geometry, Galois representations, elliptic fibrations, genus 3 curves and bad reduction, harmonic analysis, symplectic groups and mould combinatorics, this volume presents a collection of papers covering a wide swath of number theory emerging from the third iteration of the international Women in Numbers conference, "Women in Numbers - Europe" (WINE), held on October 14-18, 2013 at the CIRM-Luminy mathematical conference center in France. While containing contributions covering a wide range of cutting-edge topics in number theory, the volume emphasizes those concrete approaches that make it possible for graduate students and postdocs to begin work immediately on research problems even in highly complex subjects.